The pillowcase cat caper - Blanco, Marivi S.; San Diego, Remus (Manila : Tahanan Books for Young Readers, 1996)
Join junior Filipino detectives Jenny and her brother Jay, in a wild cat caper that will catapult young readers to the edge of their seats!
Primary
Keywords: Mystery and detective stories; Fantasy; Cats -- Juvenile fiction